(untitled) (Journal of history, 2022)
On the basis of archival data, the article examines the situation of Kazakh refugees who migrated from the famine and Holodomor of 1928-1933 within Kazakhstan and from Kazakhstan to neighboring countries. As a result of the meat tax imposed by the Soviet government on the population, the number of livestock in Kazakhstan sharply decreased, which led to starvation and death of millions of Kazakh people, who were deprived of means of subsistence (consisting mainly of meat and dairy products). In search of a way to survive, hundreds of thousands of Kazakh nomads, who migrated from places inhabited for centuries, fell into the trap of fate, becoming refugees. The data presented in the article once again confirm that our nation, who were victims of the famine of 1929-1933, lost their national culture, and their social situation worsened. The rich, mullahs andhunger refugees – Kazakh refugees who previously inhabited the Mangistau peninsula, migrated through Turkmenistan along the coast of the Caspian Sea, fled from the punishment of the Soviet government in the 1930s and famine to the territory of Irancalled “Mazandaran”. After years of settlement, villages where Kazakhs mostly settlednearby cities of the province – Gorgan, Bundar, Turkmen and Gombad-i-Kaus, secluded from the local population, the Turkmens called “Kazakh village”. Eventually, these villages merged with the mentioned cities and joined the territory of the city. The article analyses the reasons for the migration of refugees from Kazakhstan to neighboring countries such as Russia, Kyrgyzstan, Uzbekistan, Turkmenistan, Iran, Afghanistan and China, also history of the survival and adaptation of refugees in other countries.